2018
DOI: 10.1038/s41419-017-0211-4
|View full text |Cite
|
Sign up to set email alerts
|

miR-27b-3p inhibits proliferation and potentially reverses multi-chemoresistance by targeting CBLB/GRB2 in breast cancer cells

Abstract: Drug resistance remains a major problem in the treatment of conventional chemotherapeutic agents in breast cancers. Owing to heterogeneity and complexity of chemoresistance mechanisms, most efforts that focus on a single pathway were unsuccessful, and exploring novel personalized therapeutics becomes urgent. By a system approach, we identified that microRNA-27b-3p (miR-27b), a miRNA deleted in breast cancer tissues and cell lines, has a master role in sensitizing breast cancer cells to a broad spectrum of anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
94
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(98 citation statements)
references
References 43 publications
4
94
0
Order By: Relevance
“…This work followed the expression analyses of miRNA profiles in our previous studies, which showed that downregulated miR‐27b was confirmed in OLP tissues when compared with tissues from healthy subjects. In a similar manner, miR‐27b was previously reported as a tumor suppressor, which was decreased or depleted in colorectal cancer, gastric cancer, breast cancer, and in oral squamous cell carcinoma . Moreover, Aghbariet et al reported decreased expressions of miR‐27b in tissues of OLP patients when compared with control samples, which was consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This work followed the expression analyses of miRNA profiles in our previous studies, which showed that downregulated miR‐27b was confirmed in OLP tissues when compared with tissues from healthy subjects. In a similar manner, miR‐27b was previously reported as a tumor suppressor, which was decreased or depleted in colorectal cancer, gastric cancer, breast cancer, and in oral squamous cell carcinoma . Moreover, Aghbariet et al reported decreased expressions of miR‐27b in tissues of OLP patients when compared with control samples, which was consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
“…For example, Matsuyama et al reported a tumor suppressive role for miR‐27b in human colon cancer cells. Chen et al showed that downregulation of miR‐27b was correlated with cell proliferation by inactivating the phosphatidylinositol‐3‐kinase/protein kinase B signaling pathways in breast cancers. In addition, Liu et al reported that decreased miR‐27b promoted oral squamous cell carcinoma cell proliferation by targeting Frizzled‐7 and contributing to tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Our data are therefore consistent with a role of miR‐27a as tumour suppressor and that its downregulation leads to an upregulation of the pro‐oncogenic CBLB and CCNG1. Interestingly, a report indicated that miR‐27b, another member of the miR‐27 family, directly targets CBLB [54], though it is not clear whether miR‐27a and miR‐27b can interact with the same mRNA targets or are cell type‐specific.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-27b-3p and miR-218-5p were another two downregulated miRNAs in our case study that are reported for the first time in melanoma. MiR-27b-3p was also downregulated in lung cancer tissues [53] and in breast cancer tissues and cell lines, where it was associated with chemoresistance [54]. However, miR-27b-3p expression was increased in Dox-resistant anaplastic thyroid cancer (ATC) cells [55].…”
Section: Discussionmentioning
confidence: 99%